Aspects of black holes in alternative theories of gravity - Benkel, Robert (2019)
Black holes are among the simplest objects in the Universe, yet they are also the perfect probes of the strong-field regime of gravity, where alternative theories of gravity are expected to yield new predictions for the physics of compact astrophysical objects. In the era of gravitational wave astronomy, some of the predictions can finally be put to a test.